Anti-Inflammatory, Anti-Arthritic and Anti-Nociceptive Activities of Nigella sativa Oil in a Rat Model of Arthritis - Cinzia Nasuti; Donatella Fedeli; Laura Bordoni; Marco Piangerelli; Maurizio Servili; Roberto Selvaggini; Rosita Gabbianelli (MDPI AG, 2019)
This study investigated the preventive efficacy of the crude oil extracted from Nigella sativa seeds in a rat model of arthritis induced by using complete Freund’s adjuvant (CFA). Nigella sativa oil at 1.82 mL/kg or 0.91 mL/kg (corresponding to 1596 and 798 mg/kg, respectively) was orally administered for 25 days from the day of immunization. One immunized group was treated orally with indomethacin (3 mg/kg) as a reference drug. Body weight growth rate, paw swelling, arthritis score, mechanical allodynia, locomotor activity and anxiety-like behavior were observed, and the levels of Interleukin 6 (IL-6), C-reactive protein, albumin and total cholesterol in plasma were measured on days 15 and 25. Nigella sativa oil showed anti-inflammatory, anti-arthritic and anti-nociceptive activities that were significant as compared to untreated arthritic rats but less than indomethacin. These results indicated that Nigella sativa oil significantly attenuated adjuvant-arthritis in rats and the higher dose (1.82 mL/kg) prevented the development of arthritis with an inhibition of 56%.